PROSPECTS FOR DIVERSIFICATION AND SUPPLY OF ENERGY OF UZBEKISTAN BASED ON WORLD EXPERIENCE - Jurayev Lazizjon Egamberdiyevich (American Journals, 2024)
Uzbekistan faces significant challenges in meeting its growing energy needs through a diversified and sustainable supply. This article examines the prospects for Uzbekistan to enhance its energy security by drawing upon the successful experiences of other countries in diversifying energy sources and improving energy efficiency. Through a comprehensive literature review and comparative analysis, the study finds that Uzbekistan has strong potential to expand its use of renewable energy, particularly solar and wind power, as well as to boost energy efficiency across the industrial, buildings, and transportation sectors.
Keywords: Uzbekistan, energy diversification, energy efficiency, renewable energy, energy security